Menentukan Jarak pada Ruang Dimensi Tiga dengan Analisis Vektor - Alghadari, Fiki (Prosiding Konferensi Nasional Penelitian Matematika dan Pembelajarannya, 2017)
This article is a study on the ways of vector concepts to determine the distance in three-dimensional space. Typically, mathematics learning has introduced three-dimensional to students at the middle school. These three-dimensional learning during ordinary was implemented by based on spatial ability, both conventional and computer-assisted learning. Student spatial intelligence is different clearly. Based on the result of several studies in the literature, especially for female students has shown that they were difficulties in the mathematical spatial problem so that there was an imbalance of learning achievement, and vector concepts can be used to help. The purpose of this article is knowing how to determine of geometrical measure on the solid using vector concepts. Vector concepts in this study as one of all of counting alternative by students high school who have spatial difficulties. Vector concepts that be used like orthogonal projection and vector in the direction normal to the plane. Using the vector concepts because of solid like cube can be drawn on three-dimensional of coordinate. On the other hand, the spatial relation like points, lines, and planes was studied in vector analysis. Using of vector concepts, student’s three-dimensional learning would not involve much of spatial ability, but student’s ability in mathematical count would have been more.